Public attitudes toward immigration – Determinants and unknowns - Mohsen Javdani (IZA World of Labor, 2020)
Public attitudes toward immigration play an important role in influencing immigration policy and immigrants' integration experience. This highlights the importance of a systematic examination of these public attitudes and their underlying drivers. Evidence increasingly suggests that while a majority of individuals favor restrictive immigration policies, particularly against ethnically different immigrants, there exists significant variation in these public views by country, education, age, and so on. In addition, sociopsychological factors play a significantly more important role than economic concerns in driving these public attitudes and differences.
Keywords: J15; J18; J7; D01; 330; immigration; public attitudes; economic concerns; sociopsychological factors